Acellular pertussis vaccine given by accelerated schedule: response of preterm infants. Issue 1 (1st January 2004) - Slack, M H; Schapira, D; Thwaites, R J; Schapira, C; Bamber, J; Burrage, M; Southern, J; Andrews, N; Miller, E
Abstract : Objective: To describe the immune response of preterm infants to a diphtheria/tetanus/three component acellular pertussis (DTaP) vaccine, under an accelerated schedule, and the effects of steroids on this response. To compare responses with those of term infants. Design: Prospective observational study. Setting: Five Wessex neonatal units; Hertfordshire immunisation clinics. Patients: Infants born at < 32 weeks; term controls. Interventions: DTaP- Haemophilus influenzae type b vaccine given at 2, 3, and 4 months. Blood taken to assess antibody responses to vaccines. Main outcome measures: IgG geometric mean concentrations (GMC) to vaccines. Results: A total of 130 preterm (mean gestational age 29.1 weeks) and 54 term infants were recruited. After the third immunisation, preterm infants had similar GMCs to controls to diphtheria, tetanus, filamentous haemagglutinin (FHA), and pertactin (PRN), but a significantly lower GMC to pertussis toxin (PT). Responses to tetanus and PRN increased with age at the third immunisation, and those to tetanus, FHA, PRN, and PT increased with gestational age at birth. Response to tetanus correlated negatively with the number of doses of antenatal steroids received. There was no association between responses and postnatal steroids. Conclusion: When immunised with a combined acellular pertussis- H influenzae type b vaccine under an accelerated schedule, IgG GMC of preterm infants to PT was reduced. GMCs to tetanus, FHA, PRN, and PT increased with gestational age at birth, and GMCs to tetanus and PRN increased with age at the third immunisation. There is, however, no benefit in delaying immunisation. Anti-tetanus IgG decreased with increasing number of doses of antenatal steroids. There was no effect for postnatal steroids.